Does the Functional Form of the Association Between Education and Mortality Differ by U.S. Region?. (2nd January 2018) - Sheehan, Connor; Montez, Jennifer Karas; Sasson, Isaac
ABSTRACT: To understand the education–mortality association among U.S. adults, recent studies have documented its national functional form. However, the functional form of education–mortality relationship may vary across geographic contexts. The four U.S. Census regions differ considerably in their social and economic policies, employment opportunities, income levels, and other factors that may affect how education lowers the risk of mortality. Thus, we documented regional differences in the functional form of the education–mortality association and examined the role of employment and income in accounting for regional differences. We used data on non-Hispanic white adults (2, 981, 672, person years) aged 45–84 in the 2000–2009 National Health Interview Survey, with Linked Mortality File through 2011 (37, 598 deaths) and estimated discrete-time hazard models. The functional form of education and adult mortality was best characterized by credentialism in the Midwest, Northeast, and for Western men. For Western women, the association was linear, consistent with the human capital model. In the South, we observed a combination of mechanisms, with mortality risk declining with each year of schooling and a step change with high school graduation, followed by steeper decline thereafter. Our work adds to the increasing body of research that stresses the importance of contexts in shaping the education–mortality relationship.